PROPERTIES OF FUZZY DITANCE ON FUZZY SET (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we introduce the definition of fuzzy distance space on fuzzy set then we study and discuss several properties of  this space after some illustrative examples are given . Furthermore we introduce the definition of fuzzy convergence, fuzzy Cauchy sequence of fuzzy point and fuzzy bounded fuzzy distance space .